Effects of a Passive Online Software Application on Heart Rate Variability and Autonomic Nervous System Balance - Rubik, Beverly (The journal of alternative and complementary medicine (New York, N.Y.), 2017)
Objective: This study investigated whether short-term exposure to a passive online software application of purported subtle energy technology would affect heart rate variability (HRV) and associated autonomic nervous system measures. Methods: This was a randomized, double-blinded, sham-controlled clinical trial (RCT). The study took place in a nonprofit laboratory in Emeryville, California. Twenty healthy, nonsmoking subjects (16 females), aged 40–75 years, participated. Quantum Code Technology ™ (QCT), a purported subtle energy technology, was delivered through a passive software application (Heart+ App) on a smartphone placed <1 m from subjects who were seated and reading a catalog. HRV was measured for 5 min in triplicate for each condition via finger plethysmography using a Food and Drug Administration medically approved HRV measurement device. Measurements were made at baseline and 35 min following exposure to the software applications. The following parameters were calculated and analyzed: heart rate, total power, standard deviation node-to-node, root mean square sequential difference, low frequency to high frequency ratio (LF/HF), low frequency (LF), and high frequency (HF). Results: Paired samples t -tests showed that for the Heart+ App, mean LF/HF decreased ( p = 9.5 × 10 –4 ), while mean LF decreased in a trend ( p = 0.06), indicating reduced sympathetic dominance. Root mean square sequential difference increased for the Heart+ App, showing a possible trend ( p = 0.09). Post–pre differences in LF/HF for sham compared with the Heart+ App were also significant ( p < 0.008) by independent t -test, indicating clinical relevance. Conclusions: Significant beneficial changes in mean LF/HF, along with possible trends in mean LF and root mean square sequential difference, were observed in subjects following 35 min exposure to the Heart+ App that was working in the background on an active smartphone untouched by the subjects. This may be the first RCT to show that specific frequencies of a purported non-Hertzian type of subtle energy conveyed by software applications broadcast from personal electronic devices can be bioactive and beneficially impact autonomic nervous system balance.